E4F1 and ZNF148 are transcriptional activators of the −57A > C and wild-type TERT promoter - Chua, Boon Haow; Zaal Anuar, Nurkaiyisah; Ferry, Laure; Domrane, Cecilia; Wittek, Anna; Mukundan, Vineeth T.; Jha, Sudhakar; Butter, Falk; Tenen, Daniel G.; Defossez, Pierre-Antoine; Kappei, Dennis

(untitled) (Genome Research, 2023)
Point mutations within the TERT promoter are the most recurrent somatic noncoding mutations identified across different cancer types, including glioblastoma, melanoma, hepatocellular carcinoma, and bladder cancer. They are most abundant at −146C > T and −124C > T, and rarer at −57A > C, with the latter originally described as a familial case, but subsequently shown also to occur somatically. All three mutations create de novo E26-specific (ETS) binding sites and result in activation of the TERT gene, allowing cancer cells to achieve replicative immortality. Here, we used a systematic proteomics screen to identify transcription factors preferentially binding to the −146C > T, −124C > T, and −57A > C mutations. Although we confirmed binding of multiple ETS factors to the mutant −146C > T and −124C > T sequences, we identified E4F1 as a −57A > C–specific binder and ZNF148 as a TERT wild-type (WT) promoter binder that showed reduced interaction with the −124C > T allele. Both proteins are activating transcription factors that bind specifically to the −57A > C and WT (at position 124) TERT promoter sequence in corresponding cell lines, and up-regulate TERT transcription and telomerase activity. Our work describes new regulators of TERT gene expression with possible roles in cancer.